Clinical Applications of Contrast-Enhanced Ultrasound in the Pediatric Work-Up of Focal Liver Lesions and Blunt Abdominal Trauma: A Systematic Review - Laugesen, Nicolaj Grønbæk; Nolsoe, Christian Pallson; Rosenberg, Jacob (Ultrasound International Open, 2017)
In pediatrics ultrasound has long been viewed more favorably than imaging that exposes patients to radiation and iodinated contrast or requires sedation. It is child-friendly and diagnostic capabilities have been improved with the advent of contrast-enhanced ultrasound (CEUS). The application of CEUS is indeed promising. However, no ultrasound contrast agent manufactured today is registered for pediatric use in Europe. The contrast agent SonoVue® has recently been approved by the FDA under the name of Lumason® to be used in hepatic investigations in adults and children. This article reviews the literature with respect to 2 specific applications of CEUS in children: 1) identification of parenchymal injuries following blunt abdominal trauma, and 2) classification of focal liver lesions. Applications were chosen through the CEUS guidelines published by the European Federation of Societies for Ultrasound in Medicine and Biology and World Federation for Ultrasound in Medicine and Biology. Literature was obtained by searching Medline and Pubmed Central (using Pubmed), Scopus database and Embase. CEUS proved to be an effective investigation in the hemodynamically stable child for identifying parenchymal injuries and for the characterization of focal liver lesions. CEUS showed comparable performance to CT and MRI with a specificity of 98% for identifying benign lesions and a negative predictive value of 100%. For the applications reviewed here, CEUS holds promising perspectives and can help reduce radiation exposure and use of iodinated contrast agents in pediatrics, thereby potentially reducing complications in routine imaging.
Keywords: paediatrics; ultrasound; contrast-enhanced ultrasound; contrast agents; microbubbles